Analysis of causes for poor persistence of CAR-T cell therapy in vivo - Kong, Yingjie; Tang, Ling; You, Yong; Li, Qing; Zhu, Xiaojian (Frontiers in Immunology, 2023)
Abstract: CAR-T cell therapy has been well researched to date because of its ability to target malignant tumor cells, and the most common of CAR-T cells are CD19 CAR-T cells, which play a large role in B-cell leukemia treatment. However, most of CAR-T cells are associated with relapse after clinical treatment, so the quality and persistence of CAR-T cells need to be improved. With continuous optimization, there have been four generations of CARs and each generation of CARs has had better quality and has been more durable than the previous generation. In addition, it is important to increase the proportion of memory cells in CAR-T cells. Besides, studies have shown that an immunosuppressive tumor microenvironment can lead to dysfunction of CAR-T cells, resulting in decreased cell proliferation and poor persistence. Thus, overcoming the challenges of immunosuppressive molecules and inhibitory cytokines in the tumor microenvironment can also improve CAR-T cell persistence. In this paper, we explored how to improve the durability of CAR-T cell therapy by improving the structure of CARs, increasing the proportion of memory CAR-T cells and improving the tumor microenvironment.